A C@MoS 2-x @S Preparation method of magnesium-sulfur battery positive electrode material

By preparing the positive electrode material of C@MoS2-x@S magnesium sulfur battery with three-dimensional network structure and nanocage stacking morphology, the problem of slow reaction kinetics and magnesium ion transport kinetics in magnesium sulfur batteries was solved, and the electrochemistry was significantly improved Cycle stability and capacity.

CN118833862BActive Publication Date: 2024-12-13ZHONGBEI UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411083942.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-08
Publication Date
2024-12-13
Estimated Expiration
2044-08-08

AI Technical Summary

Technical Problem

The existing magnesium-sulfur battery positive electrode materials have problems such as slow reaction kinetics, slow magnesium ion transport kinetics, poor electrochemical cycle stability, and small electrochemical cycle capacity.

Method used

Using the preparation method of C@MoS2-x@S magnesium sulfur battery positive electrode material, stirring, sonication, addition of thiourea and melamine, two-stage high-temperature calcination, washing and Dry, and finally mix with sulfur in a polytetrafluoroethylene reactor to form a carbon frame and molybdenum sulfide nanosheet with a three-dimensional network structure and nanocage stacked morphology, providing fast charge distribution and magnesium ion transport channels to avoid active materials Loss.

Benefits of technology

The reaction kinetics and magnesium ion transport kinetics are significantly accelerated, the electrochemical cycle stability and capacity are improved, and the utilization rate and structural stability of active substances are achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118833862B_ABST
    Figure CN118833862B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of magnesium-sulfur batteries, in particular to a C@MoS 2‑x A method for preparing a positive electrode material of a magnesium-sulfur battery at C@S is implemented by the following steps: step 1: dispersing sodium molybdate hexahydrate in an acidic aqueous solution of sodium chloride to obtain a uniform solution A; step 2: dispersing thiourea in the mixed solution to obtain a uniform solution B; step 3: adding the uniform solution B to the uniform solution A to obtain a white powder; step 4: placing the white powder obtained in step 3 in a tubular furnace for two-stage high-temperature calcination to obtain a black powder; step 5: placing the black powder obtained in step 4 in deionized water to obtain an intermediate product; step 6: mixing the intermediate product obtained in step 5 with sulfur to obtain C@MoS 2‑x @S magnesium-sulfur battery positive electrode material. The present invention effectively solves the problems of slow reaction kinetics, slow magnesium ion transmission kinetics, poor electrochemical cycle stability and small electrochemical cycle capacity of existing magnesium-sulfur battery positive electrode materials, and is suitable for the preparation of magnesium-sulfur batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of magnesium-sulfur batteries, in particular to a C@MoS 2-x @S Preparation method of magnesium-sulfur battery positive electrode material. Background Art

[0002] Due to population growth and changes in lifestyle, global energy demand is expected to double by 2050. However, the large-scale application of lithium batteries for electrical energy storage, the most prominent energy storage technology, is hampered by the regionality of lithium supply, high manufacturing costs and safety issues. Further improvement of energy storage technology requires breakthroughs in material systems and battery design. In terms of environmental friendliness, safety and resource reserves, magnesium batteries are a very promising green energy storage technology after lithium batteries. At present, magnesium batteries can be divided into many types according to different positive electrode materials. Among them, magnesium-sulfur batteries with sulfur as the positive electrode material have become a very promising emerging energy storage system due to their excellent energy density (3221Wh / L). However, due to the slow solid-phase diffusion rate of the doubly charged magnesium ions themselves and the "shuttle effect" of the sulfur positive electrode, the existing magnesium-sulfur battery positive electrode materials cannot achieve fast charge distribution during charging and discharging, resulting in slow reaction kinetics, and cannot provide fast magnesium ion transmission channels, resulting in slow magnesium ion transmission kinetics. On the third hand, the loss and agglomeration of active materials cannot be avoided, resulting in poor electrochemical cycle stability and small electrochemical cycle capacity. Based on this, it is necessary to invent a C@MoS 2-x @S A method for preparing a positive electrode material for a magnesium-sulfur battery is provided to solve the problems of slow reaction kinetics, slow magnesium ion transport kinetics, poor electrochemical cycle stability, and small electrochemical cycle capacity of existing positive electrode materials for magnesium-sulfur batteries. Summary of the invention

[0003] In order to solve the problems of slow reaction kinetics, slow magnesium ion transmission kinetics, poor electrochemical cycle stability and small electrochemical cycle capacity of existing magnesium-sulfur battery cathode materials, the present invention provides a C@MoS 2-x @S Preparation method of magnesium-sulfur battery positive electrode material.

[0004] The present invention is achieved by adopting the following technical solutions:

[0005] A C@MoS 2-x @S A method for preparing a positive electrode material for a magnesium-sulfur battery, the method being implemented by the following steps:

[0006] Step 1: Disperse sodium molybdate hexahydrate in an acidic aqueous solution of sodium chloride, stir at room temperature for 30 minutes at a stirring speed of 4000 r / min to obtain a uniform solution A;

[0007] The sodium chloride acidic aqueous solution is a mixture of sodium chloride aqueous solution and hydrofluoric acid;

[0008] The mass concentration of the hydrofluoric acid is 35% to 40%;

[0009] Step 2: Disperse thiourea in the mixed solution, stir at room temperature for 30 min at a stirring speed of 4000 r / min to obtain a uniform solution B;

[0010] The mixed liquid is a mixture of deionized water and ammonia water;

[0011] The mass concentration of the ammonia water is 22% to 27%;

[0012] Step 3: Add the homogeneous solution B to the homogeneous solution A, perform ultrasonic treatment for 2h~3h, the ultrasonic frequency is 40kHz, then add melamine, stir for 30min, the stirring speed is 4000r / min, freeze-dry, and obtain a white powder;

[0013] Step 4: placing the white powder obtained in step 3 in a tube furnace for two-stage high-temperature calcination to obtain a black powder;

[0014] Step 5: Place the black powder obtained in step 4 into deionized water, stir for 1 hour, wash, vacuum filter, and dry to obtain an intermediate product;

[0015] Step 6: Mix the intermediate product obtained in step 5 with sulfur, encapsulate it in a polytetrafluoroethylene reactor, heat it, cool it, wash it, and dry it to obtain C@MoS 2-x @SMagnesium-sulfur battery positive electrode material.

[0016] Furthermore, in the step 1, the amount of sodium molybdate hexahydrate is 0.34 g, the amount of sodium chloride acidic aqueous solution is 10 mL, the amount of sodium chloride is 15 g, and the amount of hydrofluoric acid is 10 μL.

[0017] Furthermore, in the step 2, the amount of thiourea used is 0.684 g, the amount of deionized water used is 10 mL, and the amount of ammonia water used is 2 mL.

[0018] Furthermore, in the step three, the amount of melamine used is 0.3 g and the drying time is 12 h.

[0019] Furthermore, in the step four, the process parameters of the two-stage high-temperature calcination are as follows: the heating rate is 2°C / min; the first stage is calcined in an argon atmosphere, the calcination temperature is 600°C, and the calcination time is 2h; the second stage is calcined in a mixed atmosphere, the calcination temperature is 800°C, and the calcination time is 2.5h; the mixed atmosphere is 95vol% argon and 5vol% hydrogen.

[0020] Furthermore, in step five, washing is performed using deionized water and ethanol solution in sequence, the drying temperature is 80° C., and the drying time is 12 hours.

[0021] Furthermore, in the step six, the mass ratio of the intermediate product obtained in step five to sulfur is 1:3, the packaging atmosphere of the polytetrafluoroethylene reactor is argon atmosphere, the heating temperature is 150°C, the heating time is 16 hours, the washing is carried out using deionized water and ethanol solution in sequence, the drying temperature is 60°C, and the drying time is 12 hours.

[0022] Compared with the existing magnesium-sulfur battery positive electrode materials, the C@MoS prepared in the present invention 2-x @S magnesium-sulfur battery positive electrode material has the following advantages: First, the C@MoS prepared in the present invention 2-x In the positive electrode material of C@MoS magnesium-sulfur battery, the in-situ generated carbon skeleton has a three-dimensional network structure and presents a nanocage stacking morphology, which is conducive to the penetration of electrolyte and provides a good electron conduction channel, thereby achieving rapid charge distribution during the charging and discharging process, thereby significantly accelerating the reaction kinetics. 2-x In the positive electrode material of the magnesium-sulfur battery, the two-dimensional layered molybdenum sulfide nanosheets with a small number of layers in situ grown on the carbon skeleton have an enlarged interlayer spacing, thereby providing a fast magnesium ion transmission channel, thereby significantly accelerating the magnesium ion transmission kinetics. 2-x @S In the positive electrode material of magnesium-sulfur battery, molybdenum sulfide (MoS) with sulfur defects 2-x ) nanosheets provide sufficient sulfur fixation sites, thereby avoiding the loss and agglomeration of active materials, thereby significantly improving the electrochemical cycle stability and electrochemical cycle capacity.

[0023] In order to verify the beneficial effects of the present invention, the C@MoS prepared by the present invention was 2-x @S magnesium-sulfur battery positive electrode materials and existing magnesium-sulfur battery positive electrode materials are tested and analyzed, such as Figure 1 to Figure 13 shown.

[0024] pass Figure 1 It can be seen that: in the C@MoS prepared by the present invention 2-x @S In the positive electrode material of magnesium-sulfur batteries, the carbon skeleton presents a cubic nanocage stacking morphology with a size distribution of 100nm~300nm.

[0025] pass Figure 2 It can be seen that: in the C@MoS prepared by the present invention 2-x @S In the positive electrode material of magnesium-sulfur batteries, the carbon skeleton has a three-dimensional network structure, which is conducive to the penetration of electrolyte and ion diffusion.

[0026] pass Figure 3It can be seen that: in the C@MoS prepared by the present invention 2-x @S In the positive electrode material of magnesium-sulfur batteries, the defective molybdenum sulfide grown in situ on the carbon skeleton is nanoscale in size, and the defective molybdenum sulfide nanoparticles are evenly dispersed on the surface of the carbon skeleton with uniform particle size and size distribution between 2nm and 4nm.

[0027] pass Figure 4 It can be seen that the C@MoS prepared by the present invention 2-x @S magnesium-sulfur battery positive electrode material and existing magnesium-sulfur battery positive electrode materials both contain sulfur diffraction peaks; among them, C@MoS prepared by the present invention 2-x @S The positive electrode material of magnesium-sulfur battery contains a broad diffraction peak of molybdenum sulfide, indicating that the degree of nano-crystallization of molybdenum sulfide is relatively high.

[0028] pass Figure 5~Figure 8 It can be seen that the C@MoS prepared by the present invention 2-x @S The C, S and Mo elements of the magnesium-sulfur battery positive electrode material are evenly distributed.

[0029] pass Fig. 9 It can be seen that the C@MoS prepared by the present invention 2-x @SThe sulfur loading of magnesium-sulfur battery positive electrode material is about 75.8%.

[0030] pass Fig.10 It can be seen that the C@MoS prepared by the present invention 2-x @SThe impedance curve radius of the magnesium-sulfur battery positive electrode material is smaller than that of the existing magnesium-sulfur battery positive electrode material, which indicates that the three-dimensional network structure of the carbon skeleton can significantly reduce the electrode impedance.

[0031] pass Fig.11 It can be seen that the C@MoS prepared by the present invention 2-x @S The electrochemical cycle capacity of the magnesium-sulfur battery positive electrode material is higher (about 740mAh / g) and the degree of polarization is smaller, which indicates that its active material utilization rate is higher, the loss of active materials is reduced, and the structure is stable.

[0032] pass Fig.12 It can be seen that at high rate current density, the C@MoS prepared by the present invention 2-x The electrochemical cycling capacity of C@MoS magnesium-sulfur battery cathode materials remains higher, which indicates that 2-x @S can significantly enhance the surface S and Mg 2+ redox kinetics.

[0033] pass Fig.13 It can be seen that: 1. During the first 50 cycles, the electrochemical cycle capacity of the existing magnesium-sulfur battery positive electrode material is relatively small and gradually increases, while the C@MoS prepared by the present invention 2-xThe electrochemical cycle capacity of the positive electrode material of C@MoS magnesium-sulfur battery does not have this phenomenon, which indicates that the C@MoS prepared by the present invention 2-x The structure of the positive electrode material of the magnesium-sulfur battery is conducive to the penetration of the electrolyte, so that the active material is fully in contact with the electrolyte, and the utilization rate of the active material is high. 2-x The electrochemical cycle capacity of the positive electrode material of the magnesium-sulfur battery is maintained at 539 mAh / g, and its retention rate is higher than that of the existing positive electrode materials of magnesium-sulfur batteries, which indicates that the loss of active substances during the cycle is reduced, thus indicating that the C@MoS prepared by the present invention 2-x @SMagnesium-sulfur battery cathode material has excellent electrochemical cycle performance.

[0034] The invention effectively solves the problems of slow reaction kinetics, slow magnesium ion transmission kinetics, poor electrochemical cycle stability and small electrochemical cycle capacity of the existing magnesium-sulfur battery positive electrode material, and is suitable for the preparation of magnesium-sulfur batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 The C@MoS prepared by the present invention 2-x @S Scanning electron microscope image of magnesium-sulfur battery positive electrode material.

[0036] Figure 2 The C@MoS prepared by the present invention 2-x @S Transmission electron microscopy of magnesium-sulfur battery cathode materials Figure 1 .

[0037] Figure 3 The C@MoS prepared by the present invention 2-x @S Transmission electron microscopy of magnesium-sulfur battery cathode materials Figure 2 .

[0038] Figure 4 The C@MoS prepared by the present invention 2-x @S XRD diagram of magnesium-sulfur battery positive electrode material and existing magnesium-sulfur battery positive electrode material.

[0039] Figure 5 The C@MoS prepared by the present invention 2-x @S Backscattered electron microscope image of magnesium-sulfur battery positive electrode material.

[0040] Figure 6 The C@MoS prepared by the present invention 2-x @SDistribution diagram of C element in magnesium-sulfur battery positive electrode material.

[0041] Figure 7 The C@MoS prepared by the present invention 2-x @SDistribution diagram of S element in magnesium-sulfur battery positive electrode material.

[0042] Figure 8 The C@MoS prepared by the present invention 2-x @S Mo element distribution diagram of magnesium-sulfur battery positive electrode material.

[0043] Fig. 9 The C@MoS prepared by the present invention 2-x @STGA spectrum of magnesium-sulfur battery positive electrode material.

[0044] Fig.10 The C@MoS prepared by the present invention 2-x @S Impedance curve of magnesium-sulfur battery positive electrode material and existing magnesium-sulfur battery positive electrode material.

[0045] Fig.11 The C@MoS prepared by the present invention 2-x @SCharge and discharge curves of magnesium-sulfur battery positive electrode material and existing magnesium-sulfur battery positive electrode material after 5 cycles at a test current density of 100mA / g.

[0046] Fig.12 The C@MoS prepared by the present invention 2-x @S Electrochemical rate performance test diagram of magnesium-sulfur battery positive electrode material and existing magnesium-sulfur battery positive electrode material under test current density of 50mA / g, 100mA / g, 1A / g, 2A / g, and 50mA / g.

[0047] Fig.13 The C@MoS prepared by the present invention 2-x @S Electrochemical cycle stability test diagram of magnesium-sulfur battery positive electrode material and existing magnesium-sulfur battery positive electrode material under the test current density of 1A / g. DETAILED DESCRIPTION Embodiment 1

[0048] A C@MoS 2-x @S A method for preparing a positive electrode material for a magnesium-sulfur battery, the method being implemented by the following steps:

[0049] Step 1: Disperse sodium molybdate hexahydrate in an acidic aqueous solution of sodium chloride, stir at room temperature for 30 minutes at a stirring speed of 4000 r / min to obtain a uniform solution A;

[0050] The sodium chloride acidic aqueous solution is a mixture of sodium chloride aqueous solution and hydrofluoric acid;

[0051] The mass concentration of the hydrofluoric acid is 35%;

[0052] Step 2: Disperse thiourea in the mixed solution, stir at room temperature for 30 min at a stirring speed of 4000 r / min to obtain a uniform solution B;

[0053] The mixed liquid is a mixture of deionized water and ammonia water;

[0054] The mass concentration of the ammonia water is 27%;

[0055] Step 3: Add the homogeneous solution B to the homogeneous solution A, perform ultrasonic treatment for 2 h at an ultrasonic frequency of 40 kHz, then add melamine, stir for 30 min at a stirring speed of 4000 r / min, and freeze-dry to obtain a white powder;

[0056] Step 4: placing the white powder obtained in step 3 in a tube furnace for two-stage high-temperature calcination to obtain a black powder;

[0057] Step 5: Place the black powder obtained in step 4 into deionized water, stir for 1 hour, wash, vacuum filter, and dry to obtain an intermediate product;

[0058] Step 6: Mix the intermediate product obtained in step 5 with sulfur, encapsulate it in a polytetrafluoroethylene reactor, heat it, cool it, wash it, and dry it to obtain C@MoS 2-x @SMagnesium-sulfur battery positive electrode material.

[0059] In the step 1, the amount of sodium molybdate hexahydrate used is 0.34 g, the amount of sodium chloride acidic aqueous solution used is 10 mL, the amount of sodium chloride used is 15 g, and the amount of hydrofluoric acid used is 10 μL.

[0060] In the step 2, the amount of thiourea used is 0.684 g, the amount of deionized water used is 10 mL, and the amount of ammonia water used is 2 mL.

[0061] In the step 3, the amount of melamine used is 0.3 g and the drying time is 12 h.

[0062] In the step 4, the process parameters of the two-stage high-temperature calcination are as follows: the heating rate is 2°C / min; the first stage is calcined in an argon atmosphere, the calcination temperature is 600°C, and the calcination time is 2h; the second stage is calcined in a mixed atmosphere, the calcination temperature is 800°C, and the calcination time is 2.5h; the mixed atmosphere is 95vol% argon and 5vol% hydrogen.

[0063] In the step 5, deionized water and ethanol solution are used for washing in sequence, the drying temperature is 80° C., and the drying time is 12 hours.

[0064] In the step six, the mass ratio of the intermediate product obtained in step five to sulfur is 1:3, the packaging atmosphere of the polytetrafluoroethylene reactor is argon atmosphere, the heating temperature is 150° C., the heating time is 16 hours, the washing is carried out using deionized water and ethanol solution in sequence, the drying temperature is 60° C., and the drying time is 12 hours. Embodiment 2

[0065] A C@MoS 2-x @S A method for preparing a positive electrode material for a magnesium-sulfur battery, the method being implemented by the following steps:

[0066] Step 1: Disperse sodium molybdate hexahydrate in an acidic aqueous solution of sodium chloride, stir at room temperature for 30 minutes at a stirring speed of 4000 r / min to obtain a uniform solution A;

[0067] The sodium chloride acidic aqueous solution is a mixture of sodium chloride aqueous solution and hydrofluoric acid;

[0068] The mass concentration of the hydrofluoric acid is 40%;

[0069] Step 2: Disperse thiourea in the mixed solution, stir at room temperature for 30 min at a stirring speed of 4000 r / min to obtain a uniform solution B;

[0070] The mixed liquid is a mixture of deionized water and ammonia water;

[0071] The mass concentration of the ammonia water is 22%;

[0072] Step 3: Add the homogeneous solution B to the homogeneous solution A, perform ultrasonic treatment for 3 h at an ultrasonic frequency of 40 kHz, then add melamine, stir for 30 min at a stirring speed of 4000 r / min, and freeze-dry to obtain a white powder;

[0073] Step 4: placing the white powder obtained in step 3 in a tube furnace for two-stage high-temperature calcination to obtain a black powder;

[0074] Step 5: Place the black powder obtained in step 4 into deionized water, stir for 1 hour, wash, vacuum filter, and dry to obtain an intermediate product;

[0075] Step 6: Mix the intermediate product obtained in step 5 with sulfur, encapsulate it in a polytetrafluoroethylene reactor, heat it, cool it, wash it, and dry it to obtain C@MoS 2-x @SMagnesium-sulfur battery positive electrode material.

[0076] In the step 1, the amount of sodium molybdate hexahydrate used is 0.34 g, the amount of sodium chloride acidic aqueous solution used is 10 mL, the amount of sodium chloride used is 15 g, and the amount of hydrofluoric acid used is 10 μL.

[0077] In the step 2, the amount of thiourea used is 0.684 g, the amount of deionized water used is 10 mL, and the amount of ammonia water used is 2 mL.

[0078] In the step 3, the amount of melamine used is 0.3 g and the drying time is 12 h.

[0079] In the step 4, the process parameters of the two-stage high-temperature calcination are as follows: the heating rate is 2°C / min; the first stage is calcined in an argon atmosphere, the calcination temperature is 600°C, and the calcination time is 2h; the second stage is calcined in a mixed atmosphere, the calcination temperature is 800°C, and the calcination time is 2.5h; the mixed atmosphere is 95vol% argon and 5vol% hydrogen.

[0080] In the step 5, deionized water and ethanol solution are used for washing in sequence, the drying temperature is 80° C., and the drying time is 12 hours.

[0081] In the step six, the mass ratio of the intermediate product obtained in step five to sulfur is 1:3, the packaging atmosphere of the polytetrafluoroethylene reactor is argon atmosphere, the heating temperature is 150° C., the heating time is 16 hours, the washing is carried out using deionized water and ethanol solution in sequence, the drying temperature is 60° C., and the drying time is 12 hours. Embodiment 3

[0082] A C@MoS 2-x @S A method for preparing a positive electrode material for a magnesium-sulfur battery, the method being implemented by the following steps:

[0083] Step 1: Disperse sodium molybdate hexahydrate in an acidic aqueous solution of sodium chloride, stir at room temperature for 30 minutes at a stirring speed of 4000 r / min to obtain a uniform solution A;

[0084] The sodium chloride acidic aqueous solution is a mixture of sodium chloride aqueous solution and hydrofluoric acid;

[0085] The mass concentration of the hydrofluoric acid is 37%;

[0086] Step 2: Disperse thiourea in the mixed solution, stir at room temperature for 30 min at a stirring speed of 4000 r / min to obtain a uniform solution B;

[0087] The mixed liquid is a mixture of deionized water and ammonia water;

[0088] The mass concentration of the ammonia water is 24%;

[0089] Step 3: Add the homogeneous solution B to the homogeneous solution A, perform ultrasonic treatment for 2.5 hours at an ultrasonic frequency of 40 kHz, then add melamine, stir for 30 minutes at a stirring speed of 4000 r / min, and freeze-dry to obtain a white powder;

[0090] Step 4: placing the white powder obtained in step 3 in a tube furnace for two-stage high-temperature calcination to obtain a black powder;

[0091] Step 5: Place the black powder obtained in step 4 into deionized water, stir for 1 hour, wash, vacuum filter, and dry to obtain an intermediate product;

[0092] Step 6: Mix the intermediate product obtained in step 5 with sulfur, encapsulate it in a polytetrafluoroethylene reactor, heat it, cool it, wash it, and dry it to obtain C@MoS 2-x @SMagnesium-sulfur battery positive electrode material.

[0093] In the step 1, the amount of sodium molybdate hexahydrate used is 0.34 g, the amount of sodium chloride acidic aqueous solution used is 10 mL, the amount of sodium chloride used is 15 g, and the amount of hydrofluoric acid used is 10 μL.

[0094] In the step 2, the amount of thiourea used is 0.684 g, the amount of deionized water used is 10 mL, and the amount of ammonia water used is 2 mL.

[0095] In the step 3, the amount of melamine used is 0.3 g and the drying time is 12 h.

[0096] In the step 4, the process parameters of the two-stage high-temperature calcination are as follows: the heating rate is 2°C / min; the first stage is calcined in an argon atmosphere, the calcination temperature is 600°C, and the calcination time is 2h; the second stage is calcined in a mixed atmosphere, the calcination temperature is 800°C, and the calcination time is 2.5h; the mixed atmosphere is 95vol% argon and 5vol% hydrogen.

[0097] In the step 5, deionized water and ethanol solution are used for washing in sequence, the drying temperature is 80° C., and the drying time is 12 hours.

[0098] In the step six, the mass ratio of the intermediate product obtained in step five to sulfur is 1:3, the packaging atmosphere of the polytetrafluoroethylene reactor is argon atmosphere, the heating temperature is 150° C., the heating time is 16 hours, the washing is carried out using deionized water and ethanol solution in sequence, the drying temperature is 60° C., and the drying time is 12 hours. Embodiment 4

[0099] A C@MoS 2-x @S A method for preparing a positive electrode material for a magnesium-sulfur battery, the method being implemented by the following steps:

[0100] Step 1: Disperse sodium molybdate hexahydrate in an acidic aqueous solution of sodium chloride, stir at room temperature for 30 minutes at a stirring speed of 4000 r / min to obtain a uniform solution A;

[0101] The sodium chloride acidic aqueous solution is a mixture of sodium chloride aqueous solution and hydrofluoric acid;

[0102] The mass concentration of the hydrofluoric acid is 38%;

[0103] Step 2: Disperse thiourea in the mixed solution, stir at room temperature for 30 min at a stirring speed of 4000 r / min to obtain a uniform solution B;

[0104] The mixed liquid is a mixture of deionized water and ammonia water;

[0105] The mass concentration of the ammonia water is 26%;

[0106] Step 3: Add the homogeneous solution B to the homogeneous solution A, perform ultrasonic treatment for 2.8 hours at an ultrasonic frequency of 40 kHz, then add melamine, stir for 30 minutes at a stirring speed of 4000 r / min, and freeze-dry to obtain a white powder;

[0107] Step 4: placing the white powder obtained in step 3 in a tube furnace for two-stage high-temperature calcination to obtain a black powder;

[0108] Step 5: Place the black powder obtained in step 4 into deionized water, stir for 1 hour, wash, vacuum filter, and dry to obtain an intermediate product;

[0109] Step 6: Mix the intermediate product obtained in step 5 with sulfur, encapsulate it in a polytetrafluoroethylene reactor, heat it, cool it, wash it, and dry it to obtain C@MoS 2-x @SMagnesium-sulfur battery positive electrode material.

[0110] In the step 1, the amount of sodium molybdate hexahydrate used is 0.34 g, the amount of sodium chloride acidic aqueous solution used is 10 mL, the amount of sodium chloride used is 15 g, and the amount of hydrofluoric acid used is 10 μL.

[0111] In the step 2, the amount of thiourea used is 0.684 g, the amount of deionized water used is 10 mL, and the amount of ammonia water used is 2 mL.

[0112] In the step 3, the amount of melamine used is 0.3 g and the drying time is 12 h.

[0113] In the step 4, the process parameters of the two-stage high-temperature calcination are as follows: the heating rate is 2°C / min; the first stage is calcined in an argon atmosphere, the calcination temperature is 600°C, and the calcination time is 2h; the second stage is calcined in a mixed atmosphere, the calcination temperature is 800°C, and the calcination time is 2.5h; the mixed atmosphere is 95vol% argon and 5vol% hydrogen.

[0114] In the step 5, deionized water and ethanol solution are used for washing in sequence, the drying temperature is 80° C., and the drying time is 12 hours.

[0115] In the step six, the mass ratio of the intermediate product obtained in step five to sulfur is 1:3, the packaging atmosphere of the polytetrafluoroethylene reactor is argon atmosphere, the heating temperature is 150° C., the heating time is 16 hours, the washing is carried out using deionized water and ethanol solution in sequence, the drying temperature is 60° C., and the drying time is 12 hours.

[0116] Although the specific embodiments of the present invention are described above, it should be understood by those skilled in the art that these are only examples, and the protection scope of the present invention is defined by the appended claims. Those skilled in the art may make various changes or modifications to these embodiments without departing from the principles and essence of the present invention, but these changes and modifications all fall within the protection scope of the present invention.

Claims

1. A C@MoS 2-x @S A method for preparing a positive electrode material for a magnesium-sulfur battery, characterized in that: This method is implemented by the following steps: Step 1: Disperse sodium molybdate hexahydrate in an acidic aqueous solution of sodium chloride, stir at room temperature for 30 minutes at a stirring speed of 4000 r / min to obtain a uniform solution A; The sodium chloride acidic aqueous solution is a mixture of sodium chloride aqueous solution and hydrofluoric acid; The mass concentration of the hydrofluoric acid is 35% to 40%; Step 2: Disperse thiourea in the mixed solution, stir at room temperature for 30 min at a stirring speed of 4000 r / min to obtain a uniform solution B; The mixed liquid is a mixture of deionized water and aqueous ammonia; The mass concentration of the ammonia water is 22% to 27%; Step 3: Add the homogeneous solution B to the homogeneous solution A, perform ultrasonic treatment for 2h~3h, the ultrasonic frequency is 40kHz, then add melamine, stir for 30min, the stirring speed is 4000r / min, freeze-dry, and obtain a white powder; Step 4: placing the white powder obtained in step 3 in a tube furnace for two-stage high-temperature calcination to obtain a black powder; Step 5: Place the black powder obtained in step 4 into deionized water, stir for 1 hour, wash, vacuum filter, and dry to obtain an intermediate product; Step 6: Mix the intermediate product obtained in step 5 with sulfur, encapsulate it in a polytetrafluoroethylene reactor, heat it, cool it, wash it, and dry it to obtain C@MoS 2-x @S magnesium-sulfur battery positive electrode material; In the step 1, the amount of sodium molybdate hexahydrate is 0.34 g, the amount of sodium chloride acidic aqueous solution is 10 mL, the amount of sodium chloride is 15 g, and the amount of hydrofluoric acid is 10 μL; In the step 2, the amount of thiourea used is 0.684 g, the amount of deionized water used is 10 mL, and the amount of ammonia water used is 2 mL; In the step 4, the process parameters of the two-stage high-temperature calcination are as follows: the heating rate is 2°C / min; the first stage is calcined in an argon atmosphere, the calcination temperature is 600°C, and the calcination time is 2h; the second stage is calcined in a mixed atmosphere, the calcination temperature is 800°C, and the calcination time is 2.5h; the mixed atmosphere is 95vol% argon and 5vol% hydrogen.

2. A C@MoS according to claim 1 2-x @S A method for preparing a positive electrode material for a magnesium-sulfur battery, characterized in that: In the step 3, the amount of melamine used is 0.3 g and the drying time is 12 h.

3. A C@MoS according to claim 1 2-x @S A method for preparing a positive electrode material for a magnesium-sulfur battery, characterized in that: In the step 5, deionized water and ethanol solution are used for washing in sequence, the drying temperature is 80° C., and the drying time is 12 hours.

4. A C@MoS according to claim 1 2-x @S A method for preparing a positive electrode material for a magnesium-sulfur battery, characterized in that: In the step six, the mass ratio of the intermediate product obtained in step five to sulfur is 1:3, the packaging atmosphere of the polytetrafluoroethylene reactor is argon atmosphere, the heating temperature is 150° C., the heating time is 16 hours, the washing is carried out using deionized water and ethanol solution in sequence, the drying temperature is 60° C., and the drying time is 12 hours.